The Relationship between Sex, Physical Activity and Body Mass Index in Thai Adult Working (ACPES Journal of Physical Education, Sport, and Health (AJPESH), 2023)
Physical Activity (PA) is associated with improved Body mass index (BMI) indicates a ratio of body weight to squared height, which is a useful health indicator. So, the objectives of this to analyze the relationship between sex with physical activity and body mass index. Thai adult working from Maha Sarakham Province University, aged 25 years and older, both males and females. The sample group consisted of 400 personnel by a sampling procedure, following Krejci And Morgan’s Sample Size Determination Table. The findings relationship between sex with physical activity. The analysis found that r = -.032 and p-value = .518, sex with body mass index found that r = -.016 and p-value = .756 and physical activity with body mass index found that r = -.076 and p-value = .128 which is higher than .05. This indicates that there is a no significant weak relationship between sex with physical activity, sex with body mass index, among Thai Adult Working. In other words, as physical activit increased, the level of body mass index should also decrease.